Elements of Clinical Examination Preparation Courses That Increase Trainee Preparedness for Clinical Examination: Narrative Review of 63 Studies - Eleanor R Gunn; Gülay Dalgic; Tanisha Jowsey; Cameron Grant; Pauline Cooper-Ioelu (Australian Journal of Clinical Education, 2026)
Introduction: High-stakes clinical examinations are key in trainee progression to specialisation. Courses may support trainees in examination preparation. Objective: To describe how preparation courses support and prepare trainees for clinical examinations, and to identify which elements of preparation courses are key. Methods: EMBASE (Ovid), PubMed, and Cochrane Central Register of Controlled Trials databases were searched for studies published between 2004 and 2024. Search terms included Medical/paediatr* AND educat /undergraduate/trainee/training AND clinical exam /exam /certification exam AND residen AND/OR prepar*. We additionally searched for four specific examinations. We also followed PRISMA guidelines and conducted a thematic analysis of the included studies. Results: Sixty-three studies were included for review. Four key themes emerged from the literature: 1) Effective pedagogy - including cognitive and social supports and technological aids; 2) Curriculum alignment; 3) Accounting for personal factors and experiences of clinical examination candidates, including clinical expertise, language factors, and mentorship; and 4) Demystifying clinical examinations through supervision factors and familiarising trainees with examination conditions through mock examinations (discussed by 54% of included studies). Conclusion: Diverse approaches to clinical examination preparation courses exist. Studies suggest that preparation courses may positively impact trainee confidence. Further research is needed to understand the effect of preparation courses on examination outcomes.